Does perceived similarity of pro-environmental behaviors lead to behavioral spillover? - Dreijerink, Lieke; Handgraaf, Michel; Antonides, Gerrit (Frontiers in Behavioral Economics, 2023)
Similarity of pro-environmental behaviors is described as a moderator of behavioral spillover: when behaviors are perceived as similar positive spillover would be more likely. However, how people perceive similarity is unclear and therefore, the exact role that similarity plays in the spillover process is uncertain. In a survey (n = 1,536) we investigated how people clustered a variety of pro-environmental behaviors and why. Moreover, we explored potential spillovers between people's current and desired behaviors. People appeared to mainly cluster behaviors according to domains (such as energy, mobility) in addition to other categorization types. Furthermore, positive spillovers from actual to desired behavior occurred both within and between domains. In other words, similarity did not seem to play an important role in predicting spillover. In general, people who clustered behaviors into more different categories had a stronger overall desire to behave pro-environmentally than people who used fewer clusters.